Bone tissue reactions to dental implants - Sh. Namjo Nik (Tehran University of Medical Sciences, 1994)
There has been a lot of development in the science of implantology since forty years ago when extensive research began on this field of science. The use of Dental Implantology has also increased in the last decade, which the main reason is the success of it. Recently some of our colleagues participate in short time Introductory and advanced courses of implant inside or outside the country and begin to use implants. Unfortunately, due to the insufficient period of time, there is no discussion of basic sciences of dental implantology. So we decided to partially fill this gap by writing this article.